THE USING OF IWBS IN MATHEMATICS CLASSROOMS BY PRIMARY SCHOOL TEACHER - Murat BAŞ (International Journal of Eurasia Social Sciences, 2015)
This study aims to explore potential answers to the question of how and why IWBs are used during mathematics classes organised by teachers in a primary schooL. Qualitative data was obtained from primary school teachers through the use of observation forms and semi-structured interviews. The results of this study indicate that despite some large class sizes, the IWBs were deemed to be successful in motivating students. However, according to findings of this study, it is highly possible to be argued that teachers used their boards for a restricted range of functions. Although they did use the IWB frequently, they encountered a series of difficulties. For instance, calibration problem of IWBs and restricted training can just be samples. Despite of these kinds of problems, most participants valued the use of IWBs overwhelmingly positively. The study concludes with some recommendations for future practice and research